Qualitative study of knowledge and attitudes of husbands in dealing with wives who have nausea and vomiting in the first trimester at PMB D - Dorma Aritonang; Nanik Yuliwati (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: Predisposing factors in the occurrence of emesis gravidarum are psychosocial factors. During pregnancy, attention from family members is needed by the mother, especially the attention of the husband. Small things that husbands do have significant meaning in improving psychological health in a better direction. Purpose of Writing: To obtain in-depth information about the husband's knowledge and attitudes in dealing with a wife who has nausea and vomiting in the first trimester at PMB D. Research Methods: This study used a qualitative method by conducting in-depth interviews (depth interviews) and FGD (Focus Group Discussion), namely to obtain in-depth information about the knowledge and attitudes of husbands in dealing with wives who have nausea and vomiting in the first trimester, so that it is possible to obtain implicit information (insight). Research Results: Knowledge of husbands in dealing with wives who have nausea and vomiting in the first trimester shows that there are still many informants who have poor knowledge about the causes, symptoms and complications of nausea and vomiting in pregnancy. The husband's attitude in dealing with his wife who had nausea and vomiting in the first trimester showed that most of the informants had a positive attitude as shown by paying attention, namely buying food such as fruit to relieve nausea, encouraging mothers to avoid spicy/sour foods, always accompanying mothers to check their pregnancy and being more understanding of what pregnant women feel. Conclusions and Suggestions: The results of this study are expected to provide health education about nausea and vomiting in pregnancy, especially husbands who are involved in the counseling process and outreach events for pregnant women classes.